Handheld Technique Compared to Deep Breathing Technique in Reducing Anxiety Before Cardiac Catheterization - Emil Huriani; Siska Prima Olimviani; Hendria Putra (Faculty of Nursing, Universitas Hasanuddin, 2021)
Introduction: Cardiac catheterization is an invasive procedure that can cause anxiety in patients. Waiting to undergo a cardiac catheterization procedure can be a major source of anxiety. This study aims to determine the effect of finger grip therapy on patient anxiety before cardiac catheterization. Methods: This research was conducted at the integrated heart center Dr. M. Djamil Padang from July 2020 - January 2021. This research is a quasi-experimental study with a pretest posttest with control group design which was conducted on 18 respondents in the control group and 18 respondents in the intervention group using simple random sampling technique and using the questionnaire research instrument State Trait Anxiety. Inventory (STAI). This study used univariate analysis and bivariate analysis. Results: The results of this study indicate a Z value of -4,853 and a Sig or P value of 0,000 <0.05, so there is a significant difference between the intervention group and the control group. Conclusion: Finger hand-held therapy is better than deep breathing techniques when dealing with anxiety in patients before cardiac catheterization at Dr. M. Djamil Padang.